Comparative study and relationship analysis between purine content, uric acid, superoxide dismutase, and growth traits in purebred and crossbred Thai native chickens - Tantiyasawasdikul, Veeraya; Chomchuen, Kitsadee; Loengbudnark, Wipas; Chankitisakul, Vibuntita; Boonkum, Wuttigrai (Frontiers in Veterinary Science, 2023)
The objective was to compare and analyze the relationship between growth, purine content, uric acid, and superoxide dismutase (SOD) in purebred and crossbred Thai native chickens. A total of 300 Thai native chickens were divided into 3 groups. Group 1 was purebred Thai native chickens (100%TN), Group 2 was 50% Thai native chickens (50%TN), and Group 3 was 25% Thai native chickens (25%TN). Data included the body weight (BW), average daily gain (ADG), and breast circumference (BrC). At 6, 8, and 10 weeks of age, 10 chickens from each group were randomly euthanized to collect breast meat, liver, and blood samples to analyze the purine content consisting of total purine, adenine, guanine, xanthine, and hypoxanthine, and uric acid, in breast meat and liver and SOD in blood. A general linear model, Pearson correlation and principal component analysis were used to analyze the significant differences and relationship between variables. The results showed the 25%TN group had the highest growth traits at every age, while the 100%TN group had the lowest (P < 0.05). Consistent with the analysis results of purine values, purine content and uric acid in breast meat and liver and SOD in blood decreased with age (P < 0.05). The correlations between purine content (total purine, adenine, guanine, xanthine, and hypoxanthine) and growth traits (BW, ADG, and BrC) ranged from moderate negative to moderate positive (-0.542 to 0.253)(P < 0.05). The correlations between uric acid and growth traits (0.348 to 0.760) and SOD and growth traits (0.132 to 0.516) were low to moderate positive with significant differences (P < 0.05). The principal component plot, which highlighted three principal components (PC 1, PC 2, and PC 3), explained 86.44% and 86.53% of the total information in breast meat and liver for selecting animals for optimal balance of the variation in the growth traits, purine content, uric acid, and SOD. Although purebred Thai native chickens showed the lowest growth traits, purine content, uric acid, and SOD were also lowest compared to crossbred Thai native chickens. Therefore, the development of genetics in Thai native chickens to produce healthy food could be possible.